Enabling Wireless Power Transfer and Multiple Antennas Selection to IoT Network Relying on NOMA - Le, Si-Phu; Nguyen, Minh-Sang Van; Do, Dinh-Thuan; Nguyen, Hong-Nhu; Nguyen, Ngoc-Long; Nguyen, Nhat-Tien; Voznak, Miroslav (Elektronika ir Elektrotechnika, 2020)
Wireless Power Transfer (WPT) is a significant technique for Internet of Things (IoT) networks. Recently, more interest has been focused on multiple access technique without orthogonal signals for wireless communication. Non-orthogonal Multiple Access (NOMA) scheme is proposed to allow users the access point in IoT network. In this paper, we propose the power beacon which is able to feed energy to power-constraint relay node to further support transmission from the source to destinations in IoT networks. In this article, a NOMA system is benefited by with WPT and antenna selection technique. The system improvement can be achieved through the exact closed-form expressions of outage probability (OP). The performance gap among two users is evaluated using model of the Rayleigh fading channels. Furthermore, we compare NOMA with traditional scheme to highlight advantage of such IoT system.